1999
DOI: 10.1161/01.cir.99.6.823
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Inositol(1,4,5)Trisphosphate Generation by Endothelin-1 During Postischemic Reperfusion

Abstract: Inhibition of Ins 1,4,5P3 generation during myocardial reperfusion by endothelin-1 represents a novel antiarrhythmic mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…ET may as a potent vasoconstrictor elicit arrhythmias secondary to coronary vasoconstriction (35, 565, 566), although observations that ET-induced ventricular arrhythmias may precede overt evidence of myocardial ischemia have led to suggestions that it could also have a direct arrhythmogenic effect (35,565). On the other hand, reperfusion of ischemic rat hearts in the presence of ET-1 did not cause the expected reperfusion-induced increase in inositol 1,4,5-trisphosphate (IP 3 ); given the proarrhythmogenic potential of IP 3 , ET-1-induced inhibition of IP 3 generation during myocardial reperfusion would represent a novel antiarrhythmic mechanism (242,627). Accordingly, given the many contradictory reports on the arrhythmogenic properties of ET-1, which may vary depending on pathophysiological concomitant events, anti-ET-1 therapy should be established with caution.…”
Section: Cardiac Endothelium and Rhythmicity Of The Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…ET may as a potent vasoconstrictor elicit arrhythmias secondary to coronary vasoconstriction (35, 565, 566), although observations that ET-induced ventricular arrhythmias may precede overt evidence of myocardial ischemia have led to suggestions that it could also have a direct arrhythmogenic effect (35,565). On the other hand, reperfusion of ischemic rat hearts in the presence of ET-1 did not cause the expected reperfusion-induced increase in inositol 1,4,5-trisphosphate (IP 3 ); given the proarrhythmogenic potential of IP 3 , ET-1-induced inhibition of IP 3 generation during myocardial reperfusion would represent a novel antiarrhythmic mechanism (242,627). Accordingly, given the many contradictory reports on the arrhythmogenic properties of ET-1, which may vary depending on pathophysiological concomitant events, anti-ET-1 therapy should be established with caution.…”
Section: Cardiac Endothelium and Rhythmicity Of The Heartmentioning
confidence: 99%
“…In addition, potential antiarrhythmic properties of ET are discussed above (see sect. III) (244,426,627).…”
Section: F Role Of Etmentioning
confidence: 99%
“…In fact, there is a relationship between an increase in IP 3 in ventricular cells and the incidence of arrhythmias 41 and IP 3 inhibition and antiarrhythmic effect in reperfused myocardium. 42 The role of Purkinje cells in initiating these IP 3 -dependent arrhythmias was not stated. In this study, by isolating and studying spontaneous Ca 2+ release events in Purkinje cells that are the substrate for the arrhythmias in this canine model, we have shown that an agent effective in blocking IP 3 receptors also is effective in reducing spontaneous Ca 2+ release events.…”
Section: Implications Of Findingsmentioning
confidence: 99%
“…Intracellular application of Ins(1,4,5)P 3 causes action potential prolongation and degeneration (9) including activation of proarrhythmic sodium-calcium exchange (10). Furthermore, arrhythmias occurring during ischemia and reperfusion correlate with cardiac Ins(1,4,5)P 3 content (11)(12)(13)(14)(15)(16)(17). In the face of evidence for a pathological role of Ins(1,4,5)P 3 in the myocardium (reviewed in Ref.…”
mentioning
confidence: 99%
“…Suppression of Ins(1,4,5)P 3 generation under physiological conditions in NCM, as previously suggested for adult rat heart (29), lends support to the view that increases in Ins(1,4,5)P 3 are deleterious to the heart (18). Direct intracellular application of Ins(1,4,5)P 3 causes action potential degeneration (9, 10) and Ins(1,4,5)P 3 generation has been shown to be related to the initiation of arrhythmias under ischemia and reperfusion conditions (11)(12)(13)(14)(15)(16)(17). It is therefore possible that the abbreviated InsP pathway present in cardiac myocytes protects the heart from Ins(1,4,5)P 3 generation and consequent arrhythmias, presumably arising from enhanced Ca 2ϩ release from the cardiac sarcoplasmic reticulum.…”
mentioning
confidence: 99%